CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE (CSRD) IN LITERATURE STUDY - Ridi, Ridi (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Corporate Social Responsibility Disclosure (CSRD) is important in a company because it is a stakeholder consideration in carrying out Sustainability Reporting as well as material for investors in investing in a company’s shares. In this study the authors conducted a literature study obtained from national and international scales of 41 journals. The data taken is then drawn general conclusions as the goals to be achieved by the author. In the results of the study, it can be concluded that as a consideration of an investor and other stakeholders that CSRD is important in making decisions about investment in companies.